Pendidikan Politik di Era Digital: Analisis Peran Media Sosial dalam Meningkatkan Kesadaran Pemilih pada Pilgub Banten 2024 - Supriatno, Eko (Universitas Mathla'ul Anwar Banten, 2024)
Digitalization has changed the way political communication works, where social media now plays an important role in influencing public opinion and winning elections. This study focuses on the use of social media in the 2024 Banten Gubernatorial Election campaign, especially in terms of political interaction and marketing by candidates. Using a qualitative approach, this study analyzes the content posted by gubernatorial candidates on Instagram, including the consistency of posting schedules, captions, hashtags, and how they interact with followers. The results show that although a consistent content strategy is important for building a political image, it does not have a direct effect on the level of user engagement on social media In addition, although gubernatorial candidates actively manage their social media accounts, they tend to make less use of direct interaction with followers such as replying to comments. Interactivity occurs more among followers or political buzzers who create their own narratives beyond the control of the candidate. These findings indicate that although social media is effective for spreading political messages, the potential for interactivity in building two-way communication between candidates and voters has not been optimally utilized. This study suggests the need for further study on the use of other platforms and political marketing strategies to strengthen communication in campaigns.